Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/jxb/ery215
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the fate of mRNA in aging seeds: protection, destruction, or slow decay?

Abstract: Aged soybean seeds show widespread cleavage of long mRNA transcripts with no particular relationship to transcript function, consistent with extant hypotheses of aging mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 63 publications
6
57
1
Order By: Relevance
“…Germability decrease is accompanied by a reduction in total RNA content and RNA integrity [ 33 , 40 , 41 ]. Fleming et al [ 42 ] demonstrated in soybean that longer transcripts were more likely to be damaged and postulated that this was due to the impact of reactive oxygen species. It has been proven that, during germination, the seeds translate stored mRNAs using stored ribosomes [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Germability decrease is accompanied by a reduction in total RNA content and RNA integrity [ 33 , 40 , 41 ]. Fleming et al [ 42 ] demonstrated in soybean that longer transcripts were more likely to be damaged and postulated that this was due to the impact of reactive oxygen species. It has been proven that, during germination, the seeds translate stored mRNAs using stored ribosomes [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RIN is an index with a value in the range one to 10 (fully degraded RNA to intact RNA) and RNA-Seq protocols typically require total RNA with a value of at least eight [82]. Analyses of seed longevity carried out using the RIN as an index in pea [83,84], soybean [85,86], carrot, crimson clover, lettuce, onion, safflower, sesame, sorghum, tomato, and watermelon [84], revealed a positive and significant correlation between seed viabilities and RIN values in most species. Moreover, the RIN decreased prior to the loss of seed viability.…”
Section: Total Rna Degradation During Seed Agingmentioning
confidence: 99%
“…Among more than 20 different types of base damage caused by hydroxyl radicals, the most prevalent oxidized base in RNA is 8-oxoguanine [57]. Nonetheless, no significant correlation was observed between seed storage time and the relative abundance of 8-oxoguanine in total RNA [86], suggesting that RNA damage occurs by random oxidative attack on the molecule.…”
Section: Total Rna Degradation During Seed Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the quantitative relationship of the At3g08030 transcript level with aging time or seed germination frequency was not determined. Recently, Fleming et al (Fleming et al, 2018b) observed fragmentation of stored mRNAs in soybean embryonic axis by transcriptomic analysis and suggested that mRNA breaks occur at random positions.…”
Section: Degradation Of Stored Mrnas Is Highly Correlated With Aging mentioning
confidence: 99%